56. Could Maturation Effect Contribute to In-hospital Mortality Improvement During COVID-19 Pandemic?. (31st December 2020) - Maki, Gina; Vahia, Amit T; Ramesh, Mayur; Arshad, Samia; Chen, Anne; Zervos, Marcus; Alangaden, George J
Abstract: Background: The surge of COVID-19 cases overwhelms hospital systems necessitating rapid learning of the disease process and management. During the course of a novel pandemic, multiple interventions are rapidly implemented to improve patient outcomes. When evaluating efficacy of individual interventions, one should account for the simultaneous improvements in knowledge and experience of healthcare providers (HCP), known as the maturation effect. We hypothesized that multiple processes rapidly implemented, along with the maturation effect would result in improved survival of COVID-19 patients hospitalized over the course of the pandemic. Methods: This retrospective study was done at Henry Ford Hospital (HFH), a 900-bed tertiary care facility in Detroit, Michigan. The first COVID-19 patient was hospitalized on March 10, 2020 followed by a rapid surge of cases. We evaluated the trends of in-hospital case fatality rate of COVID-19 PCR positive patients through April 28, 2020. Time-points of sequential implementation of key measures for the management of COVID-19 patients were recorded. Results: A total of 1023 COVID-19 patients were hospitalized during the study period with 165 deaths (16 %). Case fatality rate during week one was 42% and down trended over time (Figure 1). Key measures were sequentially implemented over the course of the study period as shown in Figure 1. These included development and implementation of in-house PCR testing, dedicated infectious diseases COVID-19 rounding teams, treatment guidelines and algorithms, and early steroid use in hypoxic patients. Figure 2 demonstrates that despite the surge of COVID-19 admissions, mortality continued to improve over time. Figure 1. Trend line of all-cause in-house morality over time Figure 2. Mortality by admission date over time Conclusion: Maturation effect takes into consideration that regardless of individual interventions, HCP improve their knowledge of the disease process and treatment over time leading to better outcomes. Our study shows the possibility of the maturation effect leading to improved survival in hospitalized COVID-19 patients. The maturation effect should be accounted for when evaluating the effect of specific interventions for COVID-19. Disclosures: Marcus Zervos, MD, Melinta Therapeutics (Grant/Research Support)